2021
DOI: 10.3390/antibiotics10020106
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Antimicrobial Use Contexts in the Poultry Sector: Challenges for Small-Scale Layer Farms in Kenya

Abstract: The poultry sector contributes significantly to Kenya’s food and economic security. This contribution is expected to rise dramatically with a growing population, urbanization, and preferences for animal-source foods. Antimicrobial resistance is putting the poultry sector in Kenya—and worldwide—at risk of production losses due to the failure of medicines for animal (and human) health. The emergence and spread of antimicrobial resistance has been linked to overuse and misuse of antimicrobials in poultry and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…The common antimicrobial classes in Timor-Leste (tetracycline, penicillin, and macrolide) are consistent with global and regional (Asia, Far East, and Oceania) usage patterns [29]. The most imported antimicrobials in Timor-Leste (oxytetracycline, amoxicillin, tylosin, and dihydrostreptomycin) were consistent with antimicrobials used in poultry and pig production in developing countries in Asia and Africa [18,50,58,59]. Oxytetracycline is popular because of its broad-spectrum action, low cost, and availability in long-acting formulations [60,61] and it is likely that similar reasons underpin its popularity in Timor-Leste.…”
Section: Antimicrobial Class and Importance For Human Medicinementioning
confidence: 60%
See 2 more Smart Citations
“…The common antimicrobial classes in Timor-Leste (tetracycline, penicillin, and macrolide) are consistent with global and regional (Asia, Far East, and Oceania) usage patterns [29]. The most imported antimicrobials in Timor-Leste (oxytetracycline, amoxicillin, tylosin, and dihydrostreptomycin) were consistent with antimicrobials used in poultry and pig production in developing countries in Asia and Africa [18,50,58,59]. Oxytetracycline is popular because of its broad-spectrum action, low cost, and availability in long-acting formulations [60,61] and it is likely that similar reasons underpin its popularity in Timor-Leste.…”
Section: Antimicrobial Class and Importance For Human Medicinementioning
confidence: 60%
“…It would be interesting to compare the results from Timor-Leste to other countries with a similar agriculture background but similar studies from such countries could not be found [10]. Although antimicrobial use levels are currently low, use may increase in the future with farming intensification, as seen in other developing countries [49,50]. In this study, there is already evidence of increasing use in the broiler industry, with import levels rising by 119% between 2018 and 2019.…”
Section: Quantity Of Antimicrobial Importmentioning
confidence: 71%
See 1 more Smart Citation
“…Our findings show that the behavioural tendency of farmers towards using antimicrobials is driven by the onset of any sign of illness in the birds, even though most of the farmers have not received any formal training on the identification of diseases and animal health management. This behaviour may explain the observed high percentage of farmers who indulge in self-prescription based on self-diagnosis, consequently risking an incorrect diagnosis and wrong use of antimicrobial drugs [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials are commonly purchased deprived of instructions, exposing incorrect practice or purschasing the wrong drug which is self-administered by un-professional i.e. farmers(Kiambi et al, 2021).The situation is made worse since human doctors and veterinarians tend to use antimicrobials to cover themselves in case of wrong diagnosis or as a the sky-rocketing levels of antimicrobial resistance experienced today. Most farmers practice mixed animal-raising; that is: they keep many types of animals; there is also close relationship between humans/farmers and their animals; so, resistant bacteria can easily be transferred across the animals and to/from humans.Eighty-one point ve percent (81.5%; 44/54) of the E. coli isolates, in this study, showed multidrug resistance; Ten (22.7%) of the multi-drug-resistant isolates were resistant to 2 antimicrobials; 15 (34.1%) were resistant to 3 antimicrobials; 8 (18.2%) to 4, while 5 (11.4%) each were resistant to 5 and 6 antimicrobials, respectively (Fig.2).…”
mentioning
confidence: 99%